Analisis Kinerja Karyawan Berdasarkan Kesehatan Mental Di Kantor Pelayanan Sewa Tanah Pemerintah Kota Bandung - Nadya Armani Salma; Najma Farisa Agustina (Jurnal Manajemen Bisnis Era Digital, 2024)
Mental health in employees refers to a psychological condition that encompasses emotional, psychological, and social well-being, affecting how they think, feel, and act in the workplace. It involves employees' ability to manage stress, work productively, contribute to the work community, and build positive relationships with colleagues. Good mental health in employees positively impacts their performance, productivity, and attendance at work. At the Land Lease Service Office of the Bandung City Government, a government agency responsible for land leasing services in the Bandung area, there are no existing programs or policies that support employee mental health. This study aims to identify the level of awareness and perceptions of employees at the Land Lease Service Office of the Bandung City Government regarding the importance of mental health and its impact on their performance, productivity, and attendance. The subjects of this research are the employees of the Land Lease Service Office of the Bandung City Government, and the object of this research is mental health concerning performance. The research method used is a case study with a qualitative research approach. Data collection techniques include interviews and questionnaires. The results of this study indicate that the mental health of employees at the Land Lease Service Office of the Bandung City Government has a significant impact on their performance, productivity, and attendance.